Please give solution of the following :-

Asked by  | 22nd Jul, 2012, 12:07: PM

Expert Answer:

Answer :  (i)  Given : f(x)= -2x + 5
To find  : The value of 2f(x)+f(-x)
 
Now ,
 f(x)= -2x + 5..................(1)

Replacing x by -x , we get ,
 f(-x)= 2x + 5 .................(2)
 
Now as asked by the question 
= 2 f(x) - f(-x) 
= 2 ( -2x + 5) - (2x+5)        {using (1) and (2) }
= -4x + 10 - 2x -5
= - 6x  + 5 Answer 
 
Note : Please ask one question at a time

Answered by  | 22nd Jul, 2012, 08:48: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.